Removal of Iron and Manganese in Groundwater using Natural Biosorbent - Fauzi, Baharudin; Mohd Yuhyi, Mohd Tadza; S. N., Mohd Imran; J., Jani (IOP Publishing, 2018)
This study was conducted to measure and compare the concentration of iron, manganese and hardness of the river and groundwater and to determine the effectiveness of iron and manganese removal by using natural biosorbent which is banana peels. The samples of river and groundwater were collected at riverbank filtration site at Jenderam Hilir, Dengkil. Based on the water quality investigation, the concentration of iron and manganese in the samples of groundwater have exceeded the drinking water quality standard which are 0.3 mg/L for iron and 0.1 mg/L for manganese. The removal process of the iron and manganese in the groundwater was done by using 2, 4 and 8 grams of banana peels activated carbon. It is found that with higher amount of activated banana peels, the removal of iron and manganese is more effective. The ranges of percentage of iron and manganese removal are between 82.25% to 90.84% and 98.79% to 99.43% respectively. From the result, banana peels activated carbon can be concluded as a one of the most effective low-cost adsorbent for groundwater treatment.